Program Kursus Calon Pengantin (Suscatin) Sebagai Bentuk Dakwah Dan Pemberdayaan Terhadap Catin Dalam Membentuk Keluarga Sakinah Di Kua Kecamatan Koto Tangah Kota Padang - Heriadi; Ulfatmi; Sarwan (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Abstract. This research seeks to systematically reveal and describe in a factual and actual manner the implementation of bridal development at the Koto Tangah District Religious Affairs Office, Padang City. This type of research is descriptive field research. Data collection techniques using interviews, observation (observation). Documentation. The research results show that the implementation of Suscatin means that every catin must follow the SOP that has been determined, including registering online. Visit the SIMKAH website https://simkah4.kemenag.go.id, by completing all the necessary requirements. The Suscatin program is carried out individually if there is a small amount of catin and group coaching if there is a large number of catin couples. Catin coaching material relates to domestic life, marriage laws, the wisdom of marriage, the rights and obligations of husband and wife, how to form a harmonious family, and how to maintain the integrity of the household to avoid divorce. The catin coaching method is a direct method, namely lecture, discussion and demonstration methods. The supporting factors for catin are the enthusiasm of the catin participants, the catin mentor who is quite competent, the delivery method is quite simple, while the inhibiting factors in catin coaching are the place of residence of the prospective bride and groom, the limited insight of the guidance participants, the lack of discipline of the participants, limited time, and limited facilities and infrastructure.